Can we still do something-and what?-for a seemingly missing syndrome? - Rita Campi; Maurizio Bonati (BMC, 2019)
Abstract Background Although several modifiable risk factors have been identified, and prone and side sleep positions were identified as preventing sudden infant death syndrome (SIDS), the epidemiology of sudden unexpected deaths in infancy (SUDI), which includes SIDS, has not unchanged in over a decade. What can be done? Methods Italian infant mortality rates were analysed between 1996 and 2015. Results Between 1996 and 2015 in Italy 1152 SUDI deaths were reported in infants less than one year old. SUDI decreased substantially from 18 in 1996 to 10.2 deaths per hundred live births in 2015 (− 43%), the contribution was the change in the SIDS rate from 11.3 to 4.1 (− 64%). However, since 1004 main and SIDS rates have not changed. Conclusion Interventions that support safe sleep must be maintained, but research is still needed since although these dramatic deaths have been reduced their causes remain unknown. The challenge is now to shift their trend which has been constant for too long.